2013
DOI: 10.1002/er.3091
|View full text |Cite
|
Sign up to set email alerts
|

N-doped titania powders prepared by different nitrogen sources and their application in quasi-solid state dye-sensitized solar cells

Abstract: SUMMARY Nitrogen‐doped TiO2 nanocrystalline particles are synthesized by a microwave‐assisted hydrothermal growth method using different amines (Dipropylamine, Diethanolamine and Ammonium hydroxide) as nitrogen sources. Characterization of the nanoparticles was performed with X‐ray diffraction, UV–vis diffuse reflectance spectroscopy, Field Emission Scanning Electron Microscopy and X‐ray Photoelectron Spectroscopy. The prepared N‐doped TiO2 nanoparticles exhibit pure anatase phase with average diameter of 9 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…TiO 2 nanoparticles with mesoporous nature offer a large internal surface area, which improves dye adsorption, leading to efficient light absorption and high photocurrent generation. Hence, high‐power conversion efficiency can be achieved compared with bulk TiO 2 material . Moreover, this mesoporous structure offers rapid electron transport at the device interface, which improves the charge transfer properties of the DSSC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 nanoparticles with mesoporous nature offer a large internal surface area, which improves dye adsorption, leading to efficient light absorption and high photocurrent generation. Hence, high‐power conversion efficiency can be achieved compared with bulk TiO 2 material . Moreover, this mesoporous structure offers rapid electron transport at the device interface, which improves the charge transfer properties of the DSSC .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, high-power conversion efficiency can be achieved compared with bulk TiO 2 material. 12 Moreover, this mesoporous structure offers rapid electron transport at the device interface, which improves the charge transfer properties of the DSSC. 13,14 There has been a considerable amount of research interest in synthesizing mesoporous titanium dioxide with high surface area.…”
Section: Introductionmentioning
confidence: 99%
“…We provided evidence of a significant contribution from the N-doped electrode to the generation of charge carriers, as a secondary current generation pathway. Although recent studies based on quasi-solid state DSSC devices demonstrated similar trends [ 35 ], no clear correlation between material properties and device performance were drawn.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, researchers' attention has been paid to the exploitation of the huge energy reservoir of the sun which is 10 4 times more than the actual consumption . The invention of the first dye‐sensitized solar cell (DSSC) by O'Regan and Grätzel in 1991 has made possible the usage of the solar cell energy, and since then ample investigations have been reported . The efficiency of the DSSC has been judged based on its ability to absorb visible light of all colors .…”
Section: Introductionmentioning
confidence: 99%